The Effect of Benson Relaxation on Decreasing the Degree of Blood Pressure in Older Adults with Hypertension - Ayatulloh, Daviq; Basri, Ahmad Hasan; Prayoga, Dimas Hadi; Priyantini, Diah (Universitas Airlangga, 2024)
Hypertension in the elderly is still a health concern to improve the quality of life of the elderly and prevent sudden death. The aim of this research is to explain how to reduce blood pressure in hypertensive patients using non-pharmacological techniques, namely Benson relaxation. This research uses a quasy-experiment research design with a pre-post test control group design. The research population was 63 elderly people with hypertension and 40 respondents were recruited as samples using purposive sampling. This research was divided into 2 groups, namely the treatment group and the control group, each with 20 respondents. The independent variable Benson's relaxation was carried out using standard operational procedures and blood pressure was measured using a spigmomanometer, stethoscope, observation sheet. Data analysis used the Wilcoxon signed rank test with a significance level of p < 0.05. The results of the study showed that giving Benson relaxation therapy to the treatment group showed a p value = 0.003, this means that there was an effect of giving Benson relaxation therapy on reducing blood pressure in the elderly. It can be concluded that Benson relaxation therapy shows a positive effect in reducing blood pressure in elderly people with hypertension. So that therapy can be applied by nurses in providing nursing interventions to the elderly to increase the use of non-pharmacological therapy